Pengaruh Integritas, Moralitas Individu, dan Whistleblowing system Pada Aparatur Desa Terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa di Kecamatan Tanggulangin Sidoarjo - Ilham Agung Santoso; Munari Munari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Village fund management plays a strategic role in supporting development and improving community welfare. However, its implementation still faces a high risk of fraud, which may undermine accountability and hinder development outcomes. This study aims to examine the influence of integrity, individual morality, and the whistleblowing system on fraud prevention in village fund management in Tanggulangin District, Sidoarjo Regency. A quantitative approach was employed with 90 village officials selected through purposive sampling from 18 villages. Data were collected using a questionnaire and analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS). The findings indicate that integrity, individual morality, and the whistleblowing system each have a significant effect on fraud prevention, with integrity showing the strongest influence. These results emphasize that fraud prevention efforts rely not only on formal oversight mechanisms but also on the personal characteristics of village officials and the availability of a trustworthy reporting system.